Challenges to the Swedish Welfare State - Lachman, Desmond; Green, J.; Hagemann, Robert; Ramaswamy, Ramana (Washington, D.C. : International Monetary Fund, 1995)
Sweden's economy in the early 1990s has been characterized by a deep recession, high unemployment, a ballooning public sector budgete deficit, and a decline in the value of the currency- developments that have raised questions about the country's capacity to sustain its comprehensive welfare state. This study provides an analysis of recent economic developments in a longer-term context and assesses their implications for future policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet